Respuesta :

Answer:

To solve the equation

2

2

+

3

3

=

3

2

x−2

+3

3−x

=3, we'll first try to rewrite it in a more convenient form. Notice that

3

=

3

1

3=3

1

, so we can rewrite the equation as:

2

2

+

3

3

=

3

1

2

x−2

+3

3−x

=3

1

Now, we can apply the property of exponents that states

+

=

a

b+c

=a

b

⋅a

c

. So, we can rewrite the equation as:

2

2

+

3

3

3

=

3

1

2

x−2

+

3

x

3

3

=3

1

2

2

+

27

3

=

3

2

x−2

+

3

x

27

=3

Now, let's express

2

2

2

x−2

 as

2

2

2

2

2

2

x

:

2

4

+

27

3

=

3

4

2

x

+

3

x

27

=3

Multiplying both sides by 4 to eliminate the fraction, we get:

2

+

108

3

=

12

2

x

+

3

x

108

=12

Multiplying both sides by

3

3

x

 to eliminate the second fraction, we get:

2

3

+

108

=

12

3

2

x

⋅3

x

+108=12⋅3

x

2

3

12

3

+

108

=

0

2

x

⋅3

x

−12⋅3

x

+108=0

Now, let

=

3

y=3

x

, then the equation becomes a quadratic equation:

2

2

12

+

108

=

0

2y

2

−12y+108=0

Divide the equation by 2:

2

6

+

54

=

0

y

2

−6y+54=0

Now, solve this quadratic equation for

y. Using the quadratic formula:

=

±

2

4

2

y=

2a

−b±

b

2

−4ac

where

=

1

a=1,

=

6

b=−6, and

=

54

c=54:

=

6

±

(

6

)

2

4

1

54

2

1

y=

2⋅1

(−6)

2

−4⋅1⋅54

=

6

±

36

216

2

y=

2

36−216

=

6

±

180

2

y=

2

−180

Since the discriminant is negative, there are no real solutions for

y, which means there are no real solutions for

3

3

x

, and consequently, no real solutions for

x. Thus, the equation

2

2

+

3

3

=

3

2

x−2

+3

3−x

=3 has

Step-by-step explanation:

Now, solve this quadratic equation for

y. Using the quadratic formula:

=

±

2

4

2

y=

2a

−b±

b

2

−4ac

where

=

1

a=1,

=

6

b=−6, and

=

54

c=54:

=

6

±

(

6

)

2

4

1

54

2

1

y=

2⋅1

(−6)

2

−4⋅1⋅54

=

6

±

36

216

2

y=

2

36−216

=

6

±

180

2

y=

2

−180

ACCESS MORE